2020
DOI: 10.1136/neurintsurg-2020-016862
|View full text |Cite
|
Sign up to set email alerts
|

Motor neuroprosthesis implanted with neurointerventional surgery improves capacity for activities of daily living tasks in severe paralysis: first in-human experience

Abstract: BackgroundImplantable brain–computer interfaces (BCIs), functioning as motor neuroprostheses, have the potential to restore voluntary motor impulses to control digital devices and improve functional independence in patients with severe paralysis due to brain, spinal cord, peripheral nerve or muscle dysfunction. However, reports to date have had limited clinical translation.MethodsTwo participants with amyotrophic lateral sclerosis (ALS) underwent implant in a single-arm, open-label, prospective, early feasibil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
111
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(111 citation statements)
references
References 22 publications
0
111
0
Order By: Relevance
“…Tables 2 , 3 list a diverse range of BCI applications exploiting EEG. Both invasive and non-invasive signal acquisitions have recently shown that reliable long-term (i.e., for at least several months) use of BCI systems is quite feasible (Saeedi et al, 2016 ; Sauter-Starce et al, 2019 ; Shahriari et al, 2019 ; Oxley et al, 2020 ).…”
Section: Challengesmentioning
confidence: 99%
See 2 more Smart Citations
“…Tables 2 , 3 list a diverse range of BCI applications exploiting EEG. Both invasive and non-invasive signal acquisitions have recently shown that reliable long-term (i.e., for at least several months) use of BCI systems is quite feasible (Saeedi et al, 2016 ; Sauter-Starce et al, 2019 ; Shahriari et al, 2019 ; Oxley et al, 2020 ).…”
Section: Challengesmentioning
confidence: 99%
“…Capturing high-fidelity cortical signals, this technology will significantly reduce the risk factors of craniotomy. A follow-up study has recently demonstrated successful implantation of the strentrode in humans for long-term neural signal recording (Oxley et al, 2020 ). The information transfer rate for strentrode-based BCI was comparable to the landmark study by Vansteensel et al with implanted electrodes (Vansteensel et al, 2016 ).…”
Section: Neuroplasticity Sensors Signal Processing Modeling Anmentioning
confidence: 99%
See 1 more Smart Citation
“…A novel approach to intracranial recording, via electrodes attached to an endovascular stent [ 55 ], is now in clinical feasibility trials. Such systems, while low bandwidth, may represent an effective solution for some individuals with severe disability [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15]. Recently, several new endovascular bioelectronic devices have been developed that exemplify the benefits of stimulating neural tissue through the vasculature [16][17][18][19]. However, these devices have stimulation leads that are wired to pulse generators or centimeter-sized inductive coils.…”
mentioning
confidence: 99%